The Protestants of Tomaszów Mazowiecki in the January Uprising - Witczak, Krzysztof Tomasz (Acta Universitatis Lodziensis. Folia Germanica, 2016)
The paper describes the participation of Tomaszów Mazowiecki’s Protestant population (of German origin) in the January Uprising (1863–1864). Special emphasis is placed upon four particularly spectacular biographies. Arthur William Benni (1839–1867) was a social revolutionary fighting for democracy in Russia and for the freedom of Poland and Italy. Dr. Karol Henryk Abraham Benni (1843–1916), known under the pseudonym ‘Henryk Wilk’, was a secret emissary and an insurgent in 1863–1864; he later became a distinguished physician, as well as a social worker and economic activist. Two protestants of German origin who fought in the January Uprising lived to their old age in the restored Republic of Poland. Karol Henryk August Sarré (1843–1927), a young January insurgent, served in the punitive detachment of the Tsarist Army, and was finally deported to Irkutsk (Siberia) for twelve years. Gustaw Glaesmann (1844–1928), a member of the national gendarmerie in 1863–1864, was deported to Siberia for 25 years. After his return from Siberia (1889) he worked as a teacher, and finally was buried in Tomaszów Mazowiecki.